Inclusion Strategies Used by the United States Newspapers Published in COCA in Representing Islam - Anggi Rizky Firdhani; Lia Maulia Indrayani; Rosaria Mita Amalia (UICELL, 2019)
This research is entitled “Inclusion Strategies Used by The United States Newspapers Published in COCA in Representing Islam”. The data of this research are sentences containing inclusion strategies in the news related to Islam, and those news are taken from the United States newspapers published in Corpus of Contemporary American English (COCA). The objectives of this research are to describe and analyze the inclusion strategies used by the United States newspapers published in COCA in representing Islam. The analysis of this research was done by using qualitative and descriptive research methods proposed by Nassaji (2015). This study uses the theory of inclusion strategies proposed by Van Leeuwen (2008). This study shows that the use of inclusion strategies such as differentiation-indifferentiation, nomination-identification, abstraction-objectivation, determination-indetermination, and association-dissociation are commonly used by US newspapers in representing Islam as a social actor in the news. The use of inclusion strategies mostly appear in negative news relating to Islam, and this causes Islam as a social actor often poorly represented in the media. Keywords: Inclusion Strategies, Representation, Islam, the United States Newspapers, COCA